Alcohol drinking and head and neck cancer risk: the joint effect of intensity and duration - Di Credico, Gioia; Polesel, Jerry; Dal Maso, Luigino; Pauli, Francesco; Torelli, Nicola; Luce, Daniele; Radoï, Loredana; Matsuo, Keitaro; Serraino, Diego; Brennan, Paul; Holcatova, Ivana; Ahrens, Wolfgang; et al. (British journal of cancer, 2020)
BACKGROUND: Alcohol is a well-established risk factor for head and neck cancer (HNC). This study aims to explore the effect of alcohol intensity and duration, as joint continuous exposures, on HNC risk. METHODS: Data from 26 case-control studies in the INHANCE Consortium were used, including never and current drinkers who drunk ≤10 drinks/day for ≤54 years (24234 controls, 4085 oral cavity, 3359 oropharyngeal, 983 hypopharyngeal and 3340 laryngeal cancers). The dose-response relationship between the risk and the joint exposure to drinking intensity and duration was investigated through bivariate regression spline models, adjusting for potential confounders, including tobacco smoking. RESULTS: For all subsites, cancer risk steeply increased with increasing drinks/day, with no appreciable threshold effect at lower intensities. For each intensity level, the risk of oral cavity, hypopharyngeal and laryngeal cancers did not vary according to years of drinking, suggesting no effect of duration. For oropharyngeal cancer, the risk increased with durations up to 28 years, flattening thereafter. The risk peaked at the higher levels of intensity and duration for all subsites (odds ratio = 7.95 for oral cavity, 12.86 for oropharynx, 24.96 for hypopharynx and 6.60 for larynx). CONCLUSIONS: Present results further encourage the reduction of alcohol intensity to mitigate HNC risk.
Keywords: Humans; Case-Control Studies; lidé středního věku; studie případů a kontrol; Alcohol Drinking; pití alkoholu; Female; rizikové faktory; mladý dospělý; dospělí; Aged; Oropharyngeal Neoplasms; Laryngeal Neoplasms; senioři; lidé; nádory úst; nádory hlavy a krku; časové faktory; Head and Neck Neoplasms; nádory orofaryngu; Adult; nádory hrtanu; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; Adolescent; Mouth Neoplasms; Aged, 80 and over; Severity of Illness Index; Young Adult; senioři nad 80 let; Smoking; mužské pohlaví; kouření; Time Factors; mladiství; Risk Factors